Diversity and conservation status of primates in the Sierras de Contamana, Peruvian Amazonia - Aquino, Rolando (2005)
This paper provides information on the diversity, abundance and conservation status of primates species that inhabit the forests of the Sierras de Contamana. We recorded 87 groups corresponding to 11 species. Saguinus mystax Spix, Ateles chamek Humboldt, Cebus apella Linnaeus and Lagothrix poeppigii Schinz were the most frequently sighted with 14, 13, 13 and 11 groups, respectively. The variation of group size was similar to those of groups in other areas, except for A. chamek whose groups in most of the cases consisted of more than 16 individuals. In the study area, highest population were observed for Cacajao calvus ucayalii Thomas (479 individuals / 100 km), L. poeppigii (178,5 individuos/100 km) and A. chamek (148,2 individuos/100 km). Most sightings occurred in high terrace forests (46%) and low hill forests (27%), constituting the habitats most frequently used by primates. Among the recorded species, C. calvus ucayalii and S. mystax are not still protected in any of the current protected natural areas of Peru.